Enhancing farm productivity, profitability, sustainability and livelihood of small farm holders through integrated farming system - KUMAR, SANJEEV; KUMAR, ABHISHEK; SHIVANI; KUMAR, SANTOSH; KUMAR, RAKESH; DUBEY, RACHNA; SHUBHA, KUMARI; SAURABH, KIRTI; MANIBHUSHAN; DAS, ANUP (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out from 2018 to 2024 at ICAR-Research Complex for Eastern Region, Patna, Bihar to evaluate eight farming system models [Field crops (FC) alone; FC + Fish + Duck; FC + Fish + Poultry; FC + Fish + Cattle; FC + Fish + Horticulture; FC + Fish + Horticulture + Duck; FC + Fish + Horticulture + Poultry; and FC + Fish + Horticulture + Cattle] with an objective to enhance productivity, improve profitability, optimize resource use through recycling, generate employment, and reduce production costs. The findings revealed that diversified integrated farming systems significantly outperformed over conventional rice (Oryza sativa L.)-wheat (Triticum aestivum L.) systems in terms of economic returns and nutrient recycling efficiency. Integrating field crops with fish, horticulture, and cattle increased system productivity by 186% compared to traditional rice-wheat system. Among the models studied, the field crops + fish + horticulture + poultry integration fetched the highest net returns and B:C ratio (₹3,04,900/ha; 2.36) and was followed by FC + Fish + Horticulture + Cattle (₹2,81,600; 1.99) but on the basis of B:C ratio FC + Fish + Horticulture (₹2,45,000; 2.31) and FC + Fish + Poultry (₹2,13,300; 2.26), respectively supersedes FC + Fish + Horticulture + Cattle combinations due to more production cost involved in raising of cattle. Contribution from pond dyke cultivation (vegetables + fruits) was found remarkable which added 3.9 tonnes rice equivalent yield (REY) with a net return of ₹52,950 from an area of 0.1 ha and made the system more profitable. An ample quantity of man-days (230–455) has been also generated in comparison with rice-wheat (128) system. Apart from these economic benefits the integrations of different components with crop also added 97.5 kg N; 114.5 kg P2O5 and 75.5 kg K2O.